Depressive comorbidity in preschool anxiety disorder. (14th March 2014) - von Klitzing, Kai; White, Lars O.; Otto, Yvonne; Fuchs, Sandra; Egger, Helen L.; Klein, Annette M.
<x xml:space="preserve">Abstract</x> Background The threshold for clinical relevance of preschool anxiety has recently come under increasing scrutiny in view of large variations in prevalence estimates. We studied the impact of presence/absence of additional depressive comorbidity (symptoms and/or diagnosis) on preschoolers with anxiety disorders in relation to clinical phenomenology, family, and peer problems compared to healthy controls. Method A population of 1738 preschoolers were screened and oversampled for internalizing symptoms from community sites, yielding a sample of 236 children. Results Using a multi‐informant approach (mother, father, teacher, child), we found evidence that children with anxiety disorders and depressive comorbidity display a greater internalizing symptom‐load, more peer problems and live in families with more psychosocial impairment (poor family functioning, family adversity, maternal mental health problems). The pure anxiety group was merely dissociable from controls with regard to internalizing symptoms and family adversity. Conclusion The presence of depressive comorbidity in anxiety disorders may mark the transition to a more detrimental and impairing disorder at preschool age.